Critical Thinking Abilities of Junior High School Students on Numeration Problems in View of Gender Differences - Tjitradi, Suphalo Samuel; Setianingsih, Rini; Manoy, Janet Trineke (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
This study aims to describe the critical thinking abilities of masculine male and feminine female junior high school students in solving numeracy problems. This type of research is qualitative research. This research was conducted on class VIII junior high school students in Banjarmasin. The subjects selected for this study were two students consisting of one masculine male student and one feminine female student with equal mathematical ability. The instruments used are gender test sheets, Mathematics Ability Test (MAT), Problem Solving Task (PST), and interview guidelines. Data analysis techniques include analysis of gender test results, analysis of math ability tests, analysis of problem-solving tasks, and analysis of interview data. The results showed that the critical thinking skills of masculine male and feminine female students on numeracy problems could fulfill the five indicators of critical thinking, namely identifying statements and questions/requests in the given situation, applying the steps used to solve the problem, concluding logically from the data submitted, clarifying the conclusions drawn and writing the final result, validating the answers obtained.